THE INFLUENCE OF INFORMATION, ORGANIZATIONAL OBJECTIVES AND TARGETS, AND EXTERNAL PRESSURE TOWARDS THE ADOPTION OF PERFORMANCE MEASUREMENT SYSTEM IN PUBLIC SECTOR - Wijaya, Anthonius H. Citra; Akbar, Rusdi (Journal of Indonesian Economy and Business, 2013)
This research studies the use of performance measurement systems (PMS) in public sector. It provides empirical evidence on the influencing factors determined by the use ofPMS in Indonesian local government. Institutional theory, especially institutional isomorphism, is utilized as a theoretical lens to further explain the findings. The factorsunder examination are information, goals and objectives of the organization and external pressure. The context of the study is the Provincial Government of Yogyakarta (includingBantul, Gunungkidul, Kulonprogo, Sleman, and the City of Yogyakarta). This research uses mixed research method and employs Partial Least Square (PLS) and ThematicContent Analysis (TCA) to analyze and interpret the data. The results shows that information and external pressures have a positive and significant effect on the use of PMSin local government operations. In turn, information regarding incentive has a positive and significant effect on the use of PMS. In short, goals and objectives of the organization,information and external pressures influence the use of PMS.Keywords: information, goals and objectives of the organization, external pressures, the use of performance measurement systems, institutional theory, mix method.